2000
DOI: 10.3168/jds.s0022-0302(00)75020-x
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Populations, Fermentation End-Products, and Aerobic Stability of Corn Silage Treated with Ammonia or a Propionic Acid-Based Preservative

Abstract: We studied the effects of ammonia treatment on microbial populations during the fermentation of corn silage. We also compared the effects of ammonia to a preservative containing buffered propionic acid and other antifungal compounds on the fermentation and aerobic stability of corn silage. In the first experiment, whole-plant corn was ensiled without treatment or treated with ammonia-N to supply an additional 0.3% N (fresh-forage basis). The addition of ammonia immediately increased silage pH and had no effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
122
1
12

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(154 citation statements)
references
References 16 publications
19
122
1
12
Order By: Relevance
“…The determinations of the neutral detergent fiber (NDF) and acid detergent fiber (ADF) were performed according to ; from the residuals from the NDF and ADF, the neutral detergent insoluble nitrogen (NDIN), and the acid detergent insoluble nitrogen (ADIN) were analysed, according to Licitra et al (1996). The lignin was determined in the samples according to Van Soest & Wine (1968) and the silica according to Van Soest & Jones (1968).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The determinations of the neutral detergent fiber (NDF) and acid detergent fiber (ADF) were performed according to ; from the residuals from the NDF and ADF, the neutral detergent insoluble nitrogen (NDIN), and the acid detergent insoluble nitrogen (ADIN) were analysed, according to Licitra et al (1996). The lignin was determined in the samples according to Van Soest & Wine (1968) and the silica according to Van Soest & Jones (1968).…”
Section: Methodsmentioning
confidence: 99%
“…The aerobic stability of the silages (expressed in hours) was evaluated through the temperature control of the silage exposed to the air, according to the adapted method of Kung Jr et al (2000). The silages of each treatment were kept in sheltered environment, without temperature control.…”
Section: Methodsmentioning
confidence: 99%
“…Selulosa merupakan salah satu komponen dalam ADF. Penurunan serat pada silage terkait dengan aktivitas enzim proteolitik dan fibrolitik dari mikrobia dan tanaman (Kung et al, 2000;Nadeau et al, 2000). Enzim-enzim tersebut bersifat labil pada suasana asam dengan aktivitas optimum pada pH 5-6 (McDonald, 1981).…”
Section: Kecernaan Adf Secara In Vivounclassified
“…Larous et al (2007) found that propionic acid at a concentration of 0.2% could inhibit the growth of Penecillium expansum completely. Inhibition of the growth of propionic acid is most effective in molds > yeast > bacteria (Kung et al, 2000). At concentration 0.1%, propionic acid completely inhibited the yield of mycelia and sclerotia of Aspergillus parasiticus (Chourasia, 1993).…”
Section: Assessment Of Anthracnose Diseases Of Mango Fruitsmentioning
confidence: 99%